The Influence of Financial Compensation, Work Environment, Workload on the Performance of East Lombok Regency Fire and Rescue Service Employees - Maulina Hasanah; Sulaimiah Sulaimiah; Djoko Suprayetno (Lafadz Jaya Publisher, 2023)
This research aims to determine the effect of financial compensation, work environment, and workload on employee performance. The type of research used is causal associative research with a quantitative approach. The population in this study were all employees of the East Lombok Regency Fire and Rescue Service. The number of samples used in this research was 73 people using a survey method with proportional random sampling technique. The data collection techniques used were interviews, documentation and distributing questionnaires containing financial compensation, work environment, workload and employee performance. The analytical tool used is Multiple Linear Regression Analysis using the SPSS 25 for Windows program. The results of data analysis show that; (1) financial compensation has a positive and significant effect on performance (2) the work environment has a positive and significant effect on performance, (3) workload has a negative and significant effect on performance.